Strategi Pengembangan Daya Tarik Wisatawan terhadap Minat Kunjung pada New Celosia Bandungan - Sri Rahayu; Nunuk Supraptini; Dian Anggraini; Risqi Fajar Ramadhan; Aditya Fulvian Mahatma (Gemawisata: Jurnal Ilmiah Pariwisata, 2025)
The Indonesian region has a wealth of natural and cultural resources that provide large capital for the tourism sector. Tourism is one of the creative economies that is currently in the development stage. New Celosia Bandungan is one of the tourist destinations that has high appeal in the Bandungan area, Central Java. This research aims to analyze strengths, weaknesses, opportunities, and threats (SWOT) as well as policy analysis that can be carried out to develop tourist attractions owned by New Celosia as a tourist destination. The method used in this research is a qualitative approach with data collection through field observations, interviews with informants, and documentation. The analysis results show that New Celosia has several strengths, such as affordable ticket prices, attractive photo spots, and complete facilities. However, weaknesses were also found, such as non-functioning rides and relatively expensive food prices. Regarding opportunities, the strategic location and increasing tourism demand provide potential for further development. On the other hand, threats such as competition with other tourist attractions and extreme weather must also be anticipated. Based on this SWOT analysis, it is recommended that New Celosia Tourism improve the management of facilities and services, as well as take advantage of existing development opportunities to increase visiting interest and competitiveness in the tourism industry.